DEVELOPMENT TENDENCIES OF THE BUILDING MATERIALS INDUSTRY IN UZBEKISTAN (Marketing Journal, 2025)
The construction materials industry and the innovative development of national industrial sectors are among the strategically important areas of the country’s economy. Currently, the intensification of competition in global markets and the growing demand for innovative products require intensive development of national industrial sectors. Modernizing the processes of raw materials and product manufacturing, increasing the volume of export -oriented products, ensuring price stability, and implementing environment ally friendly and energy -saving technologies have been identified as key priorities in the construction materials industry.
Keywords: efficiency; innovative development; activation; mechanisms; building materials; infrastructure; economics; industry; export -oriented products; eco - friendly technologies; global market competition; modernization. 196